Pemberdayaan Petani Menuju Desa Mandiri Benih - Cahyati Setiani; Munir E Wulanjari; Teguh Prasetyo (Jurnal Riset Agribisnis dan Peternakan, 2018)
The achievement of the rice production target in 2016 of 76.23 million tons requires concrete efforts to increase productivity, one of which can be achieved through the use of certified superior varieties of seeds. In an effort to meet the needs of seeds in each region/village, a nursery group was developed to produce seeds, namely through the activities of empowering farmers to seed independent villages using the field school approach. The study was conducted in two farmer groups located in Sidowayah Village, Klaten Regency, and Pucangrejo Village, Kendal Regency. The purpose of this study was to obtain a strategy of empowering farmers towards independent seed villages. The research method uses a qualitative approach that is exploratory. The results showed that: i) technological innovation through the Field School (SL) approach could increase farmers' knowledge in producing quality seeds, ii) limited capital was one of the obstacles to independent seed villages, iii) empowering farmers requires active involvement from Field Agricultural Instructors ( PPL) and Plant Pest Control Organizers (PPOPT). Based on the results of the study it can be concluded that the strategy of empowering farmers towards independent seed villages requires technological innovation and access to sources of capital